Padrões de distribuição do gênero Aegla Leach, 1820 (Crustacea, Decapoda, Anomura) associados à cobertura do solo - Gonçalves, Alberto Senra (2015)
Knowing the distributional patterns and the mechanisms that lead to the actual levels of diversity and richness is a challenge given the ecosystems threats. Understanding how the threats coming from the human actions can affect this diversity is the key to protect ecosystems and species. This study toward (i) investigate the richness distribution patterns of the genus Aegla in four freshwater ecoregions in South America, as well as (ii) the mechanisms that lead to that distribution, and (iii) the human influences in these freshwater ecosystems. The study area comprised four freshwater ecoregions: Upper Uruguay, Low Uruguay, Laguna dos Patos, and Tramandaí-Mampituba. Through data from five scientific collections, UFRGS, UFSM, FZB-RS, PUC-RS, and URI-Erechim, we compiled 30 species of Aegla. We associated the species distribution in four ecoregions to the distributional patterns, conservation status, environmental and spatial variables, rugosity, and land cover. The protected area network not effectively protects the aquatic ecosystems. The species richness is associated to average values of rugosity. Finally, the species occurrence areas exhibit land cover categories of agriculture and urban areas. We consider the levels of endemism inside the protected area network are key factor to conservation of aquatic ecosystems. Historic process linked to the river network formation, in a spatial context, is an important approach to understand the distributional pattern of some freshwater groups. These patterns are associated to spatial questions, following the increasing of agriculture and urban lands, are committing the diversity in freshwater environments.